Estratégia de manejo da irrigação com água salobra e cobertura morta vegetal no desempenho agronômico de genótipos de amendoim - Canjá, Juvenaldo Florentino (2021)
The use of brackish waters in agriculture represents a promising approach to resolve conflicts over multiple uses of water, which have been exacerbated by the effects of climate change. When associated with other practices, such as covering the soil with vegetable remains, brackish waters can increase the production of crops in the Brazilian semiarid region. The study aimed to evaluate the physiological performance, growth, production, accumulation and partition of photoassimilates, as well as efficiency in the use of water in two genotypes of peanut culture irrigated with brackish water and soil cover in the reproductive phase. The experiment was carried out from October to December 2019, under protected environment conditions, following the design of randomized blocks in a 2 x 2 x 2 factorial scheme - two electrical conductivities of irrigation water (0.9 and 5.0 dS m-1), two peanut genotypes (AC 130 and BR-1 cv.) and the presence and absence of soil cover, with four replications. The leaf gas exchange variables were evaluated at 48 and 63 DAS. The determination of dry matter accumulation and production was carried out at 48 and 72 DAS, respectively, and from these variables the rates of absolute, relative growth and liquid assimilation were determined, as a percentage of dry matter partition in different plant organs. . The salinity impacted the production more than the water use efficiency in the two peanut genotypes, with the relative reduction in production being greater in BR-1 cv. Covering the soil with dead plant material reduced the effects of salinity on production and increased the efficiency of water use, only in the AC 130 genotype. The highest ECw (5.0 dS m-1) negatively influenced physiological parameters, such as consequent reduction in the accumulation of dry matter, partition and growth rates, and at 48 DAS, a greater decrease in cv. BR-1 and, at 72 DAS, there was an inverse behavior. On the other hand, the application of plant material in the soil promoted beneficial effects on the analyzed variables.